The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1159/000496733
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing Psychotropic Drugs from Participants in Randomized Controlled Trials: A Systematic Review

Abstract: Background and Objective: Methods and justifications for discontinuing psychotropic drugs in randomized controlled trials (RCTs), and RCTs’ acknowledgement of possible withdrawal symptoms following discontinuation, have not been examined systematically, which this review aims to do. Study Eligibility, Data Extraction, and Synthesis: Publications in MEDLINE, EMBASE, and PsycINFO (2000–2017) randomly assigning participants diagnosed with mental disorders to discontinue antipsychotic, antidepressant, anticonvulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…8 The picture is further complicated, however, because any trial examining 'relapse' as an outcome of stopping antidepressants could be conflating relapse with withdrawal symptoms. 9 Various naturalistic cohort studies show that long-term antidepressant use has worse outcomes than short-term antidepressant use or non-pharmacological treatments. 10,11 Moreover, it appears to be difficult to stop antidepressants after extended use; 12 some patients using antidepressants may develop dependency 13 and patients using antidepressants long term report feeling addicted.…”
mentioning
confidence: 99%
“…8 The picture is further complicated, however, because any trial examining 'relapse' as an outcome of stopping antidepressants could be conflating relapse with withdrawal symptoms. 9 Various naturalistic cohort studies show that long-term antidepressant use has worse outcomes than short-term antidepressant use or non-pharmacological treatments. 10,11 Moreover, it appears to be difficult to stop antidepressants after extended use; 12 some patients using antidepressants may develop dependency 13 and patients using antidepressants long term report feeling addicted.…”
mentioning
confidence: 99%
“…16 The alternative word "discontinuation" was promoted by the pharmaceutical industry to ensure that selective serotonin reuptake inhibitors (SSRIs) were not seen by physicians and the public as addictive, [17][18][19] but reports of contemporary RCTs use both words interchangeably; "withdrawal" is more common in studies of benzodiazepines and stimulants, "discontinuation" in studies of antidepressants and antipsychotics. 20 To reduce ambiguity, distinguishing between the action of reducing or stopping a drug (discontinuation) and the ensuing signs, symptoms and experiences (withdrawal) seems appropriate.…”
Section: Psychotropic Drug Discontinuation and Withdrawal Effectsmentioning
confidence: 99%
“…39,40 In discontinuation RCTs, attitudes and behavior of study personnel and clinical attendants are sometimes reported to have important effects on the outcomes of (especially institutionalized) patients' discontinuations. 20 First-person accounts also suggest that the economic ability to suspend one's usual duties may determine the success of discontinuation. 50 Knowledge on psychosocial contributions ("set" and "setting") to prescribed drug effects is not fully organized, 51 and rarely do RCTs complement their findings with direct evaluations of treatments by participants in their own words.…”
Section: Psychotropic Drug Discontinuation and Withdrawal Effectsmentioning
confidence: 99%
See 2 more Smart Citations